N-Heterocycle-Substituted Hexa-peri-Hexabenzocoronenes with Windmill Architectures - Mörsel, Sven; Ritterhoff, Christian; Kellner, René; Meyer, Bernd; Hirsch, Andreas (Chemistry - A European Journal, 2025)
We describe the synthesis and computational investigation of N-heterocycle-substituted hexa-peri-hexabenzocoronenes (HBCs). Following our method for the preparation of thioether-substituted HBCs, we prepared pyrrole-, indole-, carbazole-, and 1H-benz[g]indole-substituted HBCs from the corresponding fluorinated precursors under microwave irradiation. A series of polysubstituted benzoindole-HBCs with windmill architectures was also synthesized using the polyfluorinated HBC analogs, and the substituent effects on the electronic properties of the HBC core were investigated. Similar to the thioether substituted HBCs, the nature of the heterocycle does not influence the optoelectronic properties of the HBC core. The attachment of multiple benzoindole substituents leads to a bathochromic shift of the absorption and emission spectra, comparable to our previous studies. Due to the circular arrangement of the benzoindole moiety, the attachment of multiple substituents results in the presence of multiple conformers at room temperature. The rotation barrier can be overcome by heating the compounds to 323–333 K. Additionally, the investigation of the relaxed geometries shows two π-stacking motifs within the conformers.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Conformational analysis; Fluorides; Hexabenzocoronene; Microwave chemistry; N-heterocycles